Attitude: is it good to be positive? / Nooryuhanis Hashim - Hashim, Nooryuhanis (2015)
People are always concern with their attitude and others’. Is it important to be very critical in choosing which attitude should one possess? The answer is yes. Attitude is formed from various factors, therefore, one can have his own judgement on which is best to be practised and this is how positive and negative attitude exist. It is learnt that experiences, beliefs and also feelings contribute much to the formation of these attitudes. Developing positive attitude elevates more meaningful achievement in one’s life, it is believed that it promotes in creating positive environment which leads one to competently socialize in a society and then results in job satisfaction, especially to the working people. This paper suggests ten strategies that can be practiced in developing positive attitude and at the same time banishing the negative one. Embracing the positive attitude leads to betterment in one’s life as it alleviates the stress that one has. Much research agreed that being positive exerts others to lead a better life, internally and externally. Thus, it is important for one to acknowledge the good and bad attitudes.